2001
DOI: 10.4049/jimmunol.167.4.2179
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Single Conserved Residue in VH Complementarity-Determining Region 2 Results in a Severe Ig Secretion Defect

Abstract: During an immune response, somatic mutations are introduced into the VH and VL regions of Ig chains. The consequences of somatic mutation in highly conserved residues are poorly understood. Ile51 is present in 91% of murine VH complementarity-determining region 2 sequences, and we demonstrate that single Ile51→Arg or Lys substitutions in the PCG1-1 Ab are sufficient to severely reduce Ig secretion (1–3% of wild-type (WT) levels). Mutant H chains, expressed in the presence of excess L chain, associate with Ig b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…This phenotype was consistent among multiple transfectants that each produced intracellular H and L chains but failed to readily form H 2 L 2 complexes (data not shown). In addition, mutant H chains displayed an association with molecular chaperones BiP and GRP94 implicating retention in the endoplasmic reticulum (data not shown), a result similar to our previous findings with Ab secretion mutants created by in vitro mutagenesis (27,57). The molecular basis of secretion loss is difficult to dissect for mutants V H 1-6 and V H 1-8 because they contain multiple mutations.…”
Section: Molecular Basis Of Altered Secretionsupporting
confidence: 71%
See 1 more Smart Citation
“…This phenotype was consistent among multiple transfectants that each produced intracellular H and L chains but failed to readily form H 2 L 2 complexes (data not shown). In addition, mutant H chains displayed an association with molecular chaperones BiP and GRP94 implicating retention in the endoplasmic reticulum (data not shown), a result similar to our previous findings with Ab secretion mutants created by in vitro mutagenesis (27,57). The molecular basis of secretion loss is difficult to dissect for mutants V H 1-6 and V H 1-8 because they contain multiple mutations.…”
Section: Molecular Basis Of Altered Secretionsupporting
confidence: 71%
“…T15 Abs are reported to undergo little affinity maturation (23,55) and in vitro studies have demonstrated that random mutations introduced into T15V H CDR2 and framework region 2 frequently resulted in loss of binding or failure to be secreted (25,26,56,57). However, group II V regions appear to be equally susceptible to harmful mutations (54,56,58).…”
Section: Deleterious Somatic Mutation Within Germinal Centersmentioning
confidence: 99%
“…However, it was an important example where deleterious secretion-impairing mutations on one variable domain can be overcome by compensatory mutations in the variable domain of the other subunit. Various groups have reported different point mutations that abolish efficient Ig assembly and secretion to date [7578]. It remains to be experimentally shown, but still is an attractive possibility to consider that somatic hypermutations are able to restore those secretion defects by introducing compensatory mutations on the other subunit.…”
Section: Russell Body Biogenesis: a Cellular Response To Biosynthementioning
confidence: 99%
“…Previously, we demonstrated that 16 mutants in the H chain framework region 2 and CDR2 region of the T15 and PCG1-1 anti-phenylphosphocholine antibodies have severe defects in secretion (6,7). The molecular basis of the secretion defect in several mutants was traced to a single substitution (Ile 51 to Arg or Lys) in the H chain of the PCG1-1 antibody (8). Mutant H chains co-immunoprecipitate with chaperones BiP and GRP94 and remain endoglycosidase H-sensitive, consistent with retention in the endoplasmic reticulum (ER).…”
Section: Engineered Antibodies and Variable Region (V-region)mentioning
confidence: 99%
“…Mutant H chains co-immunoprecipitate with chaperones BiP and GRP94 and remain endoglycosidase H-sensitive, consistent with retention in the endoplasmic reticulum (ER). Mutant H chains rapidly assemble into intracellular H 2 intermediates but exhibit impaired L chain association and undergo intracellular degradation (8).…”
Section: Engineered Antibodies and Variable Region (V-region)mentioning
confidence: 99%